Nipple-Areolar Complex Reconstruction Principles and Clinical Techniques (Springer International Publishing, 2018)
This book, written by leading international experts, deals exclusively with reconstruction techniques for the Nipple-Areolar Complex (NAC). The first chapters present the history of the Nipple-Areolar Complex reconstruction and the anatomy of this part of the body. After discussing the abnormalities of the Nipple-Areolar Complex and how to prevent Nipple-Areolar Complex disorders, the book provides extensive documentation on techniques for correcting nipple hypertrophy, nipple inversion, and for increasing nipple projection. Readers will also find helpful information of malposition and tumors of the Nipple-Areolar Complex, as well as complications that can arise during the various surgical techniques. The book offers an invaluable guide for residents and fellow, practicing and highly experienced plastic surgeons, general surgeons, and those in cosmetic surgical subspecialites. .